Escherichia coli associated urinary tract infection: Epidemiology and possible strategies for control - Subhojeet Biswas; Ramakanta Rana; Madhusmita Bal; Sanghamitra Pati; Mrutyunjay Suar; Manoranjan Ranjit (​​​One Health Bulletin)
Urinary tract infection (UTI) is a prevalent condition that individuals may experience at least once in their lifetime. It is one of the most common reasons for hospital visits across all age groups, from neonates to adults. The predominant organism causing UTIs is Escherichia (E.) coli, followed by other microorganisms such as Klebsiella pneumoniae, Staphylococcus saprophyticus, Citrobacter spp., Pseudomonas aeruginosa, and Proteus spp. This review focuses on E. coli as the predominant causative agent for UTIs, examining its contribution to the disease burden and antibiotic susceptibility which significantly impact on human health and society. Additionally, we discuss novel approaches to combat this common threat, including the development of bio-markers for UTI treatment, the application of AI, and nanotechnology in medical field to fight against UTIs. We also observe the global distribution of uropathogenic E. coli, with specific attention to India, and highlight the recent trends in drug resistance patterns among the uropathogenic E. coli isolates enabling physicians to administer appropriate antibiotics for UTI treatment.